2023
DOI: 10.1001/jama.2023.20435
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Referral, Behavioral Counseling, and Preventive Interventions for Oral Health in Children and Adolescents Aged 5 to 17 Years

Roger Chou,
Christina Bougatsos,
Jessica Griffin
et al.

Abstract: ImportanceDental caries is common in children and adolescents aged 5 to 17 years and potentially amenable to primary care screening and prevention.ObjectiveTo systematically review the evidence on primary care screening and prevention of dental caries in children and adolescents aged 5 to 17 years to inform the US Preventive Services Task Force.Data SourcesMEDLINE, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews (to October 3, 2022); surveillance through July 21, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…The disparate burden of dental caries among young children has prompted recommendations for primary care clinicians to provide preventive oral care for children 5 years and younger, including referral to a dentist . A 2023 systematic review by the US Preventive Services Task Force concluded that there is insufficient evidence for oral health (OH) screening, counseling, referrals, and preventive interventions performed by primary care clinicians in reducing dental caries. The few retrospective cohort studies that have examined the effectiveness of nondental clinicians delivering preventive OH services to young children enrolled in Medicaid have also been inconclusive …”
Section: Introductionmentioning
confidence: 99%
“…The disparate burden of dental caries among young children has prompted recommendations for primary care clinicians to provide preventive oral care for children 5 years and younger, including referral to a dentist . A 2023 systematic review by the US Preventive Services Task Force concluded that there is insufficient evidence for oral health (OH) screening, counseling, referrals, and preventive interventions performed by primary care clinicians in reducing dental caries. The few retrospective cohort studies that have examined the effectiveness of nondental clinicians delivering preventive OH services to young children enrolled in Medicaid have also been inconclusive …”
Section: Introductionmentioning
confidence: 99%